Holistic evaluation of aircraft detection lighting systems for wind turbines in Germany using a multi-method evaluation framework - Weigel, Paul; Viebahn, Peter; Fischedick, Manfred (Frontiers in Energy Research, 2022)
Transponder-based Aircraft Detection Lighting Systems (ADLS) are increasingly used in wind turbines to limit beacon operation times, reduce light emissions, and increase wind energy acceptance. The systems use digital technologies such as receivers of digital transponder signals, LTE/5G, and other information and communication technology. The use of ADLS will be mandatory in Germany both for new and existing wind turbines with a height of >100 m from 2023 (onshore) and 2024 (offshore), so a nationwide rollout is expected to start during 2022. To fully realize the benefits while avoiding risks and bottlenecks, a thorough and holistic understanding of the efforts required and the impacts caused along the life cycle of an ADLS is essential. Therefore, this study presents the first multi-aspect holistic evaluation of an ADLS. A framework for evaluating digital applications in the energy sector, previously developed by the authors, is refined and applied. The framework is based on multi-criteria analysis (MCA), life cycle assessment (LCA), and expert interviews. On an aggregated level, the MCA results show an overall positive impact from all stakeholders’ perspectives. Most positive impacts are found in the society and politics category, while most negative impacts are of technical nature. The LCA of the ADLS reveals a slightly negative impact, but this impact is negligible when compared to the total life cycle impact of the wind turbines of which the ADLS is a part. Besides the aggregated evaluation, detailed information on potential implementation risks, bottlenecks, and levers for life cycle improvement are presented. In particular, the worldwide scarcity of the required semiconductors, in combination with the general lack of technicians in Germany, lead to the authors’ recommendation for a limited prolongation of the planned rollout period. This period should be used by decision-makers to ensure the availability of technical components and installation capacities. A pooling of ADLS installations in larger regions could improve plannability for manufacturers and installers. Furthermore, an ADLS implementation in other countries could be supported by an early holistic evaluation using the presented framework.